Practical Issues in Delivery of Clinician-to-Patient Telemental Health in an Academic Medical Center. Issue 3 (May 2017) - Abrams, Jessica; Sossong, Sarah; Schwamm, Lee H.; Barsanti, Lauren; Carter, Michael; Kling, Naomi; Kotarski, Meghan; Leddy, Jaclyn; Meller, Benjamin; Simoni, Marcy; Sullivan, Michael; Wozniak, Janet
Abstract: Background: In the age of online communication, psychiatric care can now be provided via videoconferencing technologies. While virtual visits as a part of telepsychiatry and telemental health provide a highly efficient and beneficial modality of care, the implementation of virtual visits requires attention to quality and safety issues. As practitioners continue to utilize this technology, issues of clinician licensing, treatment outcomes of virtual visits versus in-person visits, and cost offset require ongoing study. Methods: This review provides an overview of the topics of technology, legal and regulatory issues, clinical issues, and cost savings as they relate to practicing psychiatry and psychology via virtual visits in an academic medical center. We review the telepsychiatry/telemental health effectiveness literature from 2013 to the present. Our literature searches used the following terms: telemental health effective, telepsychiatry effective, telepsychiatry efficacy, and telemental health efficacy. These searches produced 58 articles, reduced to 16 when including only articles that address effectiveness of clinician-to-patient services. Results: The technological, legal, and regulatory issues vary from state to state and over time. The emerging research addressing diverse populations and disorders provides strong evidence for the effectiveness of telepsychiatry. Cost savings are difficult to precisely determine and depend on the scope of the cost and benefit measured. Conclusion: Establishing a telepsychiatry program requires a comprehensive approach with up-to-date legal and technological considerations.